Population genetic structure of Sri Lankan backyard chicken flocks: Implication for conservation and genetic improvement programs - Samaraweera, A.M.; Silva, P.; Abeykone, N.D.F.; Ibrahim, Mohamed N.M.; Okeyo Mwai, Ally; Han Jianlin (American Society of Animal Science, 2014)
Traditional ‘random’ sampling strategy for molecular characterization has revealed low genetic differentiation and weak genetic structure among Asian and African indigenous, non-descript chicken populations although they carried high within-population phenotypic and molecular genetic diversity. In the present study, 192 backyard chickens collected following a nearly ‘complete’ sampling strategy for all adult birds within flocks of 75 households in five villages at two sites in Sri Lanka were genotyped using 20 microsatellite markers. The phenotypes and history of these birds were also recorded. A link of phenotypic composition and flock size with specific genetic structure of the backyard chicken populations was explored. The results suggest that the households who used to keep large flocks of indigenous backyard chickens of mixed genotypes should be included in in-situ conservation program to effectively maintain and sustainably utilize these important chicken genetic resources.